Knowing the unknown: The underestimation of monkeypox cases. Insights and implications from an integrative review of the literature - Bragazzi, Nicola Luigi; Woldegerima, Woldegebriel Assefa; Iyaniwura, Sarafa Adewale; Han, Qing; Wang, Xiaoying; Shausan, Aminath; Badu, Kingsley; Okwen, Patrick; Prescod, Cheryl; Westin, Michelle; Omame, Andrew; Converti, Manlio; et al. (Frontiers in Microbiology, 2022)
Monkeypox is an emerging zoonotic disease caused by the monkeypox virus, which is an infectious agent belonging to the genus Orthopoxvirus. Currently, commencing from the end of April 2022, an outbreak of monkeypox is ongoing, with more than 43,000 cases reported as of 23 August 2022, involving 99 countries and territories across all the six World Health Organization (WHO) regions. On 23 July 2022, the Director-General of the WHO declared monkeypox a global public health emergency of international concern (PHEIC), since the outbreak represents an extraordinary, unusual, and unexpected event that poses a significant risk for international spread, requiring an immediate, coordinated international response. However, the real magnitude of the burden of disease could be masked by failures in ascertainment and under-detection. As such, underestimation affects the efficiency and reliability of surveillance and notification systems and compromises the possibility of making informed and evidence-based policy decisions in terms of the adoption and implementation of ad hoc adequate preventive measures. In this review, synthesizing 53 papers, we summarize the determinants of the underestimation of sexually transmitted diseases, in general, and, in particular, monkeypox, in terms of all their various components and dimensions (under-ascertainment, underreporting, under-detection, under-diagnosis, misdiagnosis/misclassification, and under-notification).